2022
DOI: 10.1128/spectrum.01354-21
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis PknK Substrate Profiling Reveals Essential Transcription Terminator Protein Rho and Two-Component Response Regulators PrrA and MtrA as Novel Targets for Phosphorylation

Abstract: Networks of gene regulation and signaling cascades are fundamental to the pathogenesis of Mycobacterium tuberculosis in adapting to the continuously changing intracellular environment in the host. M. tuberculosis protein kinase K is a transcription regulator that responds to diverse environmental signals and facilitates stress-induced growth adaptation in culture and during infection. This study identifies multiple signaling interactions of PknK and provides evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…S2). Recent studies have revealed the involvement of M. tb PknK in regulating PrrA and MtrA RRs, which are essential for mycobacterial growth and survival (11, 12, 32). However, very little is known about the O -phosphorylation of HKs through the Ser/Thr protein kinases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2). Recent studies have revealed the involvement of M. tb PknK in regulating PrrA and MtrA RRs, which are essential for mycobacterial growth and survival (11, 12, 32). However, very little is known about the O -phosphorylation of HKs through the Ser/Thr protein kinases.…”
Section: Resultsmentioning
confidence: 99%
“…We also show STPK-mediated phosphorylation of a mycobacterial histidine kinase. PhoR is subjected to O-phosphorylation by M. tb Ser/Thr Protein kinase K (PknK), a soluble / membrane-associated kinase, that has multiple TCS RRs as targets (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We establish Ser/Thr phosphorylation of the toxin component as means to disrupt TA complex formation, rendering the toxin to inhibit growth and initiate persistence. The upregulation of rel and pknK transcripts under conditions of nitrogen starvation (34, 35) suggests that these cellular environments may be where PknK-mediated phosphorylation of Rel proteins is most physiologically relevant. We predict that other STPKs may similarly act to modify the TA proteins under different activating environments.…”
Section: Discussionmentioning
confidence: 99%
“…All three loci have been characterized as bona fide TA modules (19) that are responsive to stress environments such as nitrogen starvation and inhibit growth by targeting translation (34). We explored a link between the Rel TA modules and PknK, a cytosolic Ser/Thr Protein Kinase (STPK) that is coincidentally also induced under nitrogen starvation (35), and is implicated in translational control mechanisms (36). We demonstrate that PknK interacts with the RelE toxin and RelJK TA proteins in vivo .…”
Section: Introductionmentioning
confidence: 99%